The impact of Social Networks on Innovation, Competitiveness and Firm Performance in the South African Context: a case study of emerging construction firms in the Free State - Ramorena, Mphulane (Bloemfontein: Central University of Technology, Free State, 2016)
Small businesses play a very important role in every economy hence their prosperity is a concern to all. In south Africa, recent researches have indicated low levels of performance and high attrition rate among small businesses. It is generally accepted that small business’s survival is threatened by their larger business counterparts that are able to utilise their vast resources to their advantage. Fortunately, research evidence suggests that the ability of small businesses to compete with their bigger counterparts lies in their ability to engage in innovative activities. However, the sustainability of such innovative activities, depends on knowing which factors drive innovation the most in small businesses. In the present study it is theorized that when emerging construction firms engage in social networks (internally and externally) and innovate, they will be more competitive and experience better firm performance. This problem is explicated in the conceptual framework from the perspective of social capital theories, especially social networks. In general terms, this study contends that, small firms can rely on their social networks (both internal and external) to innovate in order to enhance their competitiveness and performance. Specifically, from social capital theory, it is argued that the resources embedded in social networks can be utilised by Emerging Construction Firms (ECFs) to be innovative and competitive for better firm performance. A literature review preceded the empirical study to fully comprehend the theoretical and conceptual underpinnings of the interaction between social networks, innovation, competitiveness and firm performance. Thereafter, 16 hypotheses were formulated based on the conceptual framework. Data were then collected from 800 ECFs graded at category 1 to 7 by the Construction Industry Development Board (CIDB) in the Free State province of South Africa. A key finding from mainstream literature is that due to resource limitations, smaller firms like ECFs will always find it difficult to compete with their big business counterparts on innovation and performance when they rely on money and tangible assets only. Literature also overwhelmingly indicates that innovation is enhanced by collaborative ability. Further, the literature reviews also strongly indicated a positive relationship between innovation and firm performance. The major empirical findings of this study are:  Strong positive relationship exists between networking, innovation and ECFs’ performance.  Both product and process innovation positively impacted ECFs’ performance. Implications of these and other findings are presented and discussed in this research thesis alongside recommendations for research, policy and practice.
Published Thesis